2016
DOI: 10.1037/abn0000200
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiology of self-face recognition in depressed adolescents with low or high suicidality.

Abstract: This study sought to test whether the neurobiology of self-processing differentiated depressed adolescents with high suicidality from those with low suicidality and healthy controls (N=119, MAGE= 14.79, SD=1.64, Min=11.3, Max = 17.8). Participants completed a visual self-recognition task in the scanner during which they identified their own or an unfamiliar adolescent face across three emotional expressions (happy, neutral or sad). A 3 Group (HS, LS, HC) by two within subject factors [2 Self conditions (self, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 85 publications
(143 reference statements)
5
50
2
1
Order By: Relevance
“…Further, a meta‐analysis of rumination in MDD, a construct related to negative self‐referential processing, found that rumination in MDD is positively associated with RSFC between the DMN (particularly the PCC) and subgenual PFC (Hamilton, Farmer, Fogelman, & Gotlib, ). As noted previously, the PCC showed aberrant activation, and both the PCC and precuneus showed reduced connectivity in adolescents with MDD and high suicidality or suicide attempts (Quevedo et al., ; Zhang, Chen, et al., 2016; Zhang, Tang, et al., 2016). However, these studies are limited in that they did not examine long‐range FC with the PCC and precuneus.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Further, a meta‐analysis of rumination in MDD, a construct related to negative self‐referential processing, found that rumination in MDD is positively associated with RSFC between the DMN (particularly the PCC) and subgenual PFC (Hamilton, Farmer, Fogelman, & Gotlib, ). As noted previously, the PCC showed aberrant activation, and both the PCC and precuneus showed reduced connectivity in adolescents with MDD and high suicidality or suicide attempts (Quevedo et al., ; Zhang, Chen, et al., 2016; Zhang, Tang, et al., 2016). However, these studies are limited in that they did not examine long‐range FC with the PCC and precuneus.…”
supporting
confidence: 60%
“…In regard to both affective experience and self‐referential processing in adolescent suicidality, one study examined brain activation during the viewing of self‐ and other emotional faces. Adolescents with MDD and high suicidality, defined by scores on a semistructured interview and clinical assessment, showed lower activation in the medial prefrontal cortex (PFC), ACC, posterior cingulate cortex (PCC), hippocampus, and amygdala compared to adolescents with MDD and low suicidality and healthy controls (Quevedo et al., ).…”
mentioning
confidence: 99%
“…Most importantly, our top findings revealed that frequent self-referencing like 'I', 'me ', and myself' (ranked 1, 2, 5, 7, 19) and negated self-referencing (ranked 35) posed an elevated risk as illustrated in literatures. (Burke et al, 2017;Quevedo et al, 2016) On the other hand, LDA topic modeling, sentiment analysis, and social determinants of health did not play critical roles for classification in our experiments. We attributed its low impact due to the variety of subreddits in the cohort, which possibly makes it challenge to effectively group certain topics for classifying suicide risk levels.…”
Section: Discussion and Limitationscontrasting
confidence: 44%
“…Lower PCC gray matter volume was found in adult SAs with MDD [145]. Decreased PCC activation was observed during cognitive control in adult SAs with psychotic mood disorders [51] and during self-referential processing in adolescent ideators with MDD [146], although adult SAs with depressive disorders, compared with HCs, showed increased PCC response when viewing knives [135].…”
Section: Posterior Structuresmentioning
confidence: 82%
“…A small percentage of studies (13.8%) included sex as a variable to assess potential interactions with STBs. Five studies (3.8%) reported sex-related findings, though no relationship with STBs [36,146,[193][194][195][196] and one study (0.8%) reported more females than males studied were SAs but reported no neuroimaging-related findings [197]. Chase et al [198], in a study that controlled for sex, noted that one participant identified as transmale.…”
Section: Future Directionsmentioning
confidence: 99%